Designing eco-feedback for gas emission detection with notification / Muhammad Amir Aufa Mohd Abdillih - Mohd Abdillih, Muhammad Amir Aufa (2021)
Gas sensing technology is widely has been used in most of the industry in the world. This is due to high demand from the industries especially those who run the oil and gas business. The difficulty to control and monitor those areas due to large-area problems may lead to the unwanted issue. Using big technology may be led to more money spending in order to build that technology. Besides, not to forget that implementing that kind of technology can lead to environmental damage and increase energy usage. Using eco-feedback technology for the gas sensing area is one of the ways to overcome that problem. Not only the technology is environmentally friendly, but it also helps the industries to monitor and detect the gas emission at the first stage. The use of an Eco-feedback web-based system to monitor and tracking gas emission while providing an email notification alert to notify people or users about the gas emission. This idea may help the person in charge to make the precaution step before the problem spread and out of control. This project will discuss some techniques that will be used in this idea. Last, this idea will provide the reader with more understanding about the proposed idea and significance from successfully implementing the technology, and able to spread awareness about how dangerous uncontrollable gas emission can be.